Epigenetic approaches for the detection of fetal DNA in maternal plasma - Tsui, Dana WY (Landes Bioscience, 2010)
The presence of fetal DNA in the plasma of pregnant women has opened up new possibilities for noninvasive prenatal diagnosis. Over the past decades, different types of fetal markers have been developed, initially based on discriminative genetic markers such as male-specific signals or paternally-inherited polymorphisms, and gradually evolved to the detection of fetal-specific transcripts or epigenetic signatures. This development has extended the coverage of the application of cell-free fetal DNA to essentially all pregnancies, regardless of the gender of the fetus or its polymorphic status. In this review, we present an overview of the development of noninvasive prenatal diagnosis through epigenetics. We introduce the basis of how fetal DNA could be detected from a large background of maternal DNA in maternal plasma based on fetal-specific DNA methylation patterns. We evaluate the methodologies involved and discuss the factors that affect the robustness of the detection. We review the progress in adopting fetal epigenetic markers for noninvasive prenatal assessment of fetal chromosomal aneuploidies and pregnancy-associated disorders. We conclude with comments on the future directions regarding the search for new fetal epigenetic markers and the clinical implementation of epigenetic approaches for noninvasive prenatal diagnosis.